(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
The catalytic activity in the hydrogen oxidation reaction has been examined for supported Pt–NbOx and Cs+/Pt–NbOx catalysts. It has been shown that the composite catalysts show higher catalytic activity than traditional catalysts with the same content of supported platinum. By XRD, XPS and electron microscopy it has been determined the active surface formation – oxygen deficient oxides NbOx.